Seeker Uncinectomy: A Randomized Controlled Cadaveric Trial. (November 2020) - Alromaih, Saud; Sumaily, Ibrahim; Alarifi, Ibrahim; Alroqi, Ahmad; Aloulah, Mohammad; Ajlan, Abdulrazag; Yaghmoor, Faris; Alsaleh, Saad
Background: Endoscopic sinus surgery is a common surgery, in which the uncinate process of the ethmoid is removed as the first surgical step. There are multiple techniques for uncinectomy. Herein we describe a new and simple uncinectomy technique. Methods: We performed a randomised controlled trial with blinded assessors. Eight cadaveric heads were used to compare the new technique to the commonly used technique; retrograde uncinectomy. The procedures were performed by 2 rhinologists, and the findings were evaluated by 2 senior rhinologists blinded to the technique and the surgeon who did. They assessed the final view of the procedure and the complications. Thereafter, they assessed the procedure for the duration and ease of each technique for teaching purposes. Results: Fifteen uncinectomies were performed, 7 using the retrograde technique, and 8 using the new technique. The mean durations were 5.64 min using the seeker uncinectomy and 7.57 min using the retrograde uncinectomy, p-value = 0.017. The completion was better in seeker uncinectomy; however, not significant statistically, p > 0.05. The complications with the new technique were inferior turbinate injury in 12.5% and natural ostium non-identification in 12.5%, p > 0.05. With retrograde uncinectomy, lacrimal injury occurred in 14.3%, p > 0.05. The ease of teaching scores was higher for the seeker uncinectomy. Conclusion: Based on this cadaveric trial, seeker uncinectomy seems to be a safe and easy to perform technique. However, injury to the inferior turbinate and missing the natural ostium must be taken into consideration. These warrant further studies on the clinical application of this procedure.